2019
DOI: 10.3390/brainsci10010009
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairments and Self-Reported Sleep in Early-Stage Parkinson’s Disease with Versus without Probable REM Sleep Behavior Disorder

Abstract: Parkinson's disease (PD) is associated with cognitive and sleep impairments. The presence of rapid eye movement (REM) sleep behavior disorder (RBD) symptoms may represent a worse disease prognosis for PD individuals. We investigated cognitive functioning and self-reported sleep in early-stage PD individuals with (n = 19) or without (n = 31) probable RBD. Probable RBD was defined as >5 on the REM Sleep Behavior Disorder Screening Questionnaire. Inhibition, visuospatial cognitive abilities, working memory, susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
(81 reference statements)
2
9
0
Order By: Relevance
“…Moreover, a partial dependence plot was presented for an input variable with the highest variable importance to visually confirm the tendency of marginal effects on the response variable. The function of partial dependence is presented in Equation (2).…”
Section: Comparing the Accuracy Of Sleep Behavior Disorder Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a partial dependence plot was presented for an input variable with the highest variable importance to visually confirm the tendency of marginal effects on the response variable. The function of partial dependence is presented in Equation (2).…”
Section: Comparing the Accuracy Of Sleep Behavior Disorder Prediction Modelmentioning
confidence: 99%
“…Parkinson’s disease (PD) is defined as a neurodegenerative disease that shows distinctive motor symptoms such as bradykinesia, rigidity, tremor at rest, and postural instability. Although traditional PD diagnosis and treatment methods have been developed with focusing on these motor symptoms, recent studies tend to focus more on the non-motor symptoms of PD [ 1 ] because it has been reported that PD patients are highly likely to experience non-motor symptoms such as cognitive dysfunction, depression, and sleep behavior disorders [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, a recent meta-analysis shows that PD with vPSG confirmed RBD diagnosis and PD-pRBD are related to disease duration, increased Hoehn and Yahr stage, and higher Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) Part III score 10 . Moreover, PD-pRBD is associated with lower cognitive performance 11 , 12 , a higher prevalence of mild cognitive impairment 13 , and faster cognitive decline 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to conduct all the test tools suggested by level II in a short time in the clinical condition. In addition, it has been reported that the impaired neuropsychological functions of PD are influenced by factors such as depression, the severity of speech disorders, and REM sleep behavior disorders in addition to the time of onset and age [ 25 , 26 ]. Therefore, in order to develop a predictive model that can distinguish PDD from other dementia types, such as AD, it is necessary to evaluate and identify the predictive accuracy of the cognitive profile while considering the depression and REM sleep behavior disorders of PD.…”
Section: Introductionmentioning
confidence: 99%